Process optimisation, nutrient stability and digestibility of green powder from spinach juice - Mansor, Syamila (2019)
The lipid group in food sciences at the University of Nottingham has recognised that ‘Chloroplast-Rich Fraction’ (CRF) are nutrients-rich. The removal of cell wall should increase its bioaccessibility. The quality of chloroplasts recovered using a blending and a screw-slow-juicing were compared. No published reports exist into the liberation of chloroplasts from their cell confines by juicing. Slow-juicing proved to be the simplest method to disrupt spinach leaf and extract intact chloroplasts, compared with the blending method with 0.3M sucrose or water, but producing a lower CRFs’ yield. There was no significant difference in nutrient quality of CRFs recovered by these three methods: α-tocopherol (around 420 µg/g dry mass (DM)); β-carotene (3.61-3.84 mg/g DM); lutein (4.25-5.37 mg/g DM); omega-3 fatty acids (around 34 mg/g DM). To overcome the limitations of the juicing method, the centrifugation stage is skipped and merely dry the filtered-juice. Drying spinach juice using spray-drying and freeze-drying shows better nutrient retention compared to oven-drying (with and without vacuum). There is no significant difference between the nutrient concentration of the spray-dried and freeze-dried juice. Encapsulation of juice using skimmed-milk powder gave full protection to β-carotene and lutein spray-dried at 195°C. A spray-dried spinach juice stored at different conditions for 56 days shows β-carotene was more susceptible to degradation compared with lutein and α-tocopherol. Under our experimental conditions, it was observed that excluding low fluorescent light intensity and vacuum packaging at 20°C did not seem to improve nutrient retention loss over time. The rate of β-carotene, lutein and α-tocopherol loss displayed first-order reaction kinetic with low activation energy (0.665, 2.650 and 13.893 kJ/mol for vacuum; 1.089, 4.923 and 14.142 kJ/mol for non-vacuum). The reaction kinetics and half-life for β-carotene, lutein and α-tocopherol at 4°C and non-vacuumed were 2.2x10-2, 1.2x10-2, and 0.8x10-2 day-1, and 32.08, 58.25 and 85.37 day, respectively. Nutrient retention post-digest is the highest in freeze- and spray-dried spinach juice. Compared with fresh cut-whole leaf, liberating more chloroplasts allows better micellarisation of lipid soluble vitamin, hence, is a much better source of nutrients. Pureeing leaf prior to exposure to the in-vitro digestion model appears to significantly improve the nutrients available for uptake (NA). The digestive stability and bioaccessibility of β-carotene and lutein from dried-juice and fresh-juice has better micellarisation than fresh cut-whole leaf and freeze-dried CRF. Dried-juice is a better source of bioaccessible nutrients compared with pureed leaf simply because you can consume less mass to get the same nutritional benefit, and more stable than fresh leaves.